Application of the DASH Diet Diet to Blood Sugar Control and Diabetes Complications - Azizah, Aulia Nur (Pt. Anagata Sembagi Education, 2025)
Diabetes mellitus (DM) is one of the global health problems with increasing prevalence and complications. Dietary interventions are one of the important pillars in diabetes management, where the Dietary Approaches to Stop Hypertension (DASH) diet is beginning to be recognized as a potential strategy. This quasi-experimental study with a pre-test and post-test control group design aims to evaluate the effect of the application of DASH modified according to local food on glycemic control and risk markers of complications in patients with type 2 diabetes mellitus in Indonesia. A total of 80 participants were divided into intervention and control groups. The intervention group followed the DASH program for 12 weeks with menu arrangements according to local food availability. Variables measured included fasting blood glucose, HbA1c, blood pressure, lipid profile, and glomerular filtration rate (eGFR). The results showed significant improvement in the intervention group, with a decrease in fasting blood glucose (−27 mg/dL), HbA1c (−1.3%), systolic blood pressure (−11.6 mmHg), LDL cholesterol, and an increase in HDL cholesterol and eGFR (p < 0.05). These findings confirm that DASH is not only effective as a hypertension control strategy, but also as a nutritional intervention to improve glycemic control and lower the risk of diabetes complications. Although the results are promising, further research with randomized clinical trial designs, larger sample counts, and longer durations is still needed to strengthen the evidence base.